PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN ORANG TUA DALAM MEMILIH SEKOLAH PADA SMP KATOLIK SANG TIMUR DI TANGERANG - Setiawan, Enno; Haryantini (Journal of Research and Publication Innovation, 2024)
This research aims to analyze the factors of Brand Image and Service Quality on Parents' Decisions in choosing a school at Sang Timur Catholic Middle School in Tangerang. The method used in this research is to use a descriptive and quantitative approach with classical assumption testing methods, hypothesis testing, t tests, F tests and data analysis techniques using multiple linear regression. The research results show that Brand Image is proven to have a positive and significant influence on Purchasing Decisions, which in this research is the parents' decision in choosing a school at Sang Timur Catholic Middle School in Tangerang. Service quality is proven to have a positive and significant influence on purchasing decisions, which in this research is the parents' decision in choosing a school at Sang Timur Catholic Middle School in Tangerang. Brand Image and Service Quality together have been proven to have a positive and significant influence on Purchasing Decisions, which in this research is the parent's decision in choosing a school at Sang Timur Catholic Middle School in Tangerang, which means that Brand Image and Service Quality together can provide contribution influence on Purchasing Decisions and this shows that if Brand Image and Service Quality are carried out and synergized well then they will be able to have a positive and significant influence in improving Purchasing Decisions, which in this research is the parents' decision in choosing a school at Sang Timur Catholic Middle School in Tangerang.